2016
DOI: 10.1111/mec.13828
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendocrine profiles associated with discrete behavioural variation in Symphodus ocellatus, a species with male alternative reproductive tactics

Abstract: The molecular mechanisms underlying phenotypic plasticity are not well understood. Identifying mechanisms underlying alternative reproductive tactics (ARTs) in species for which the behavioural and fitness consequences of this variation are well characterized provides an opportunity to integrate evolutionary and mechanistic understanding of the maintenance of variation within populations. In the ocellated wrasse Symphodus ocellatus, the behavioural phenotypes of three distinct male morphs (sneakers, satellites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 95 publications
3
23
0
Order By: Relevance
“…We found that each peacock blenny phenotype has a distinct transcriptomic profile (Figure a), indicating that distinct behavioural repertoires are associated with distinct neurogenomic states, which differentiate not only sex but also male morphs. These results are consistent with previous studies that have already described this parallel between specific behavioural states and neurogenomic states at different timescales (reviewed in Zayed & Robinson, ; Harris & Hofmann, ; Cardoso, Teles, & Oliveira, ), and with previous reports of specific brain transcriptomic profiles among species with ARTs for alternative male morphs, particularly in teleost fishes (Aubin‐Horth et al., ; Fraser et al., ; Nugent et al., ; Partridge et al., ; Schunter et al., ; Stiver et al., ). For example, in bluegill sunfish ( Lepomis macrochirus ), the three male ARTs, encompassing two distinct life histories, presented distinct neurogenomic profiles, with sneaker males having the most divergent expression profile, while parental males were further discriminated in the analysis relatively to their reproductive state (i.e., spawning vs. nonspawning; Partridge et al., ).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We found that each peacock blenny phenotype has a distinct transcriptomic profile (Figure a), indicating that distinct behavioural repertoires are associated with distinct neurogenomic states, which differentiate not only sex but also male morphs. These results are consistent with previous studies that have already described this parallel between specific behavioural states and neurogenomic states at different timescales (reviewed in Zayed & Robinson, ; Harris & Hofmann, ; Cardoso, Teles, & Oliveira, ), and with previous reports of specific brain transcriptomic profiles among species with ARTs for alternative male morphs, particularly in teleost fishes (Aubin‐Horth et al., ; Fraser et al., ; Nugent et al., ; Partridge et al., ; Schunter et al., ; Stiver et al., ). For example, in bluegill sunfish ( Lepomis macrochirus ), the three male ARTs, encompassing two distinct life histories, presented distinct neurogenomic profiles, with sneaker males having the most divergent expression profile, while parental males were further discriminated in the analysis relatively to their reproductive state (i.e., spawning vs. nonspawning; Partridge et al., ).…”
Section: Discussionsupporting
confidence: 92%
“…with ARTs for alternative male morphs, particularly in teleost fishes (Aubin-Horth et al, 2005;Fraser et al, 2014;Nugent et al, 2016;Partridge et al, 2016;Schunter et al, 2014;Stiver et al, 2015). For example, in bluegill sunfish (Lepomis macrochirus), the three male ARTs, encompassing two distinct life histories, presented distinct neurogenomic profiles, with sneaker males having the most divergent expression profile, while parental males were further discriminated in the analysis relatively to their reproductive state (i.e., spawning vs. nonspawning; Partridge et al, 2016).…”
Section: Brain Transcriptomic Architecture Of Alternative Reproductmentioning
confidence: 99%
See 1 more Smart Citation
“…Differences in 11‐kt between flutamide‐ and vehicle‐injected nesting males were assessed by two‐tailed t test in r (R Development Core Team, ) with α < 0.05. We focus here on 11‐kt and did not measure testosterone in this study, as testosterone does not appear to play a major role in nesting male‐specific behaviours (Nugent et al, ; Stiver et al, ), consistent with 11‐kt as the dominant androgen in teleosts (Kindler, Philipp, Gross, & Bahr, ; Rodgers, Earley, & Grober, ). Ocellated wrasses are relatively small (e.g., nesting males are ~7–9 cm standard length).…”
Section: Methodsmentioning
confidence: 97%
“…Flutamide competitively inhibits the natural ligands of the AR, and when AR inhibition occurs in the testes, it is associated with a decrease in testicular androgen production. Nesting males have naturally elevated levels of 11‐ketotestosterone, the primary testicular androgen in teleost fishes, compared to satellite or sneaker males (Nugent, Stiver, Alonzo, & Hofmann, ). However, nesting males injected with flutamide in this study showed reduced circulating 11‐ketotestosterone compared to control males only injected with the vehicle.…”
mentioning
confidence: 99%